Salivary cortisol awakening levels are reduced in human subjects with intermittent explosive disorder compared with controls. (May 2023) - Meruelo, Alejandro D.; Timmins, Matthew A.; Irwin, Michael R.; Coccaro, Emil F.
Abstract: Background: The role of the hypothalamic-pituitary-adrenal (HPA) axis in human aggressive behavior is poorly characterized, though some studies report that, unlike depression, circulating or salivary levels of cortisol are low compared with controls. Methods: In this study, we collected three salivary cortisol levels (two in the morning and one in the evening) on three separate days in 78 adult study participants with (n = 28) and without (n = 52) prominent histories of impulsive aggressive behavior. Plasma C-Reactive Protein (CRP) and Interleukin-6 (IL-6) were also collected in most study participants. Aggressive study participants meet DSM-5 criteria for Intermittent Explosive Disorder (IED) while non-aggressive participants either had a history of a psychiatric disorder or no such history (Controls). Results: Morning, but not evening, salivary cortisol levels were significantly lower in IED (p < 0.05), compared with control, study participants. In addition, salivary cortisol levels correlated with measures of trait anger (partial r = −0.26, p < 0.05) and aggression (partial r = −0.25, p < 0.05) but not with measures of impulsivity, psychopathy, depression, history of childhood maltreatment, or other tested variables that often differ in individuals with IED. Finally, plasma CRP levels correlated inversely with morning salivary cortisol levels (partial r = −0.28, p < 0.05); plasma IL-6 levels showed a similar, though not statistically significant (r p = −0.20, p = 0.12) relationship with morning salivary cortisol levels. Conclusion: The cortisol awakening response appears to be lower in individuals with IED compared with controls. In all study participants, morning salivary cortisol levels correlated inversely with trait anger, trait aggression, and plasma CRP, a marker of systemic inflammation. This suggests the present of a complex interaction between chronic-low level inflammation, the HPA axis, and IED that warrants further investigation. Highlights: HPA-axis dysfunction is evident in many behavioral disorders including those who display aggressive behavior. Lower levels of morning cortisol may be linked with aggression, but not in Intermittent Explosive Disorder (IED). 78 adults provided 3 saliva samples/day for cortisol and 3 samples for plasma CRP/IL-6 over an overlapping period. Morning, but not evening, cortisol levels were lower in IED and were inversely related to anger/aggression and CRP levels. This suggests a complex interaction between chronic inflammation, the HPA axis, and IED that warrants further investigation.